PENGARUH MODEL PEMBELAJARAN BERBASIS WEB DAN MINAT BELAJAR TERHADAP LISTENING COMPREHENSION SISWA KELAS XI MADRASAH ALIYAH AL-HIDAYAH KARANGTANJUNG – PANDEGLANG - Trisna Sonjaya Trisna Sonjaya (NIAGARA Scientific Journal, 2016)
This research aims to determine: (1) the influence of web-based learning models and interest in learning on students' listening comprehension; (2) the influence of web-based learning models and high interest in learning on students' listening comprehension; (3) the effect of web-based learning models and low learning interest on students' listening comprehension; (4) the effect of interaction between learning interest and web-based learning models on students' listening comprehension. The research results show that there is a significant influence with the web-based learning model and interest in learning on students' listening comprehension based on test results (Fcount = 4.188 ˃ Ftable = 0.351), there is a significant influence with the web-based learning model and high interest in learning on students' listening comprehension ( Fcount = 4,950 ˃ Ftable = 0.132), there is a significant influence with the web-based learning model and low interest in learning on students' listening comprehension (Fcount = 4,047 ˃ Ftable = 0.789), and there is a significant interaction effect between interest in learning and the web-based learning model on students' listening comprehension (Fcount = 4.188 ˃ Ftable = 0.175).